Proteomic Analysis of a Poplar Cell Suspension Culture Suggests a Major Role of Protein S-Acylation in Diverse Cellular Processes - Srivastava, Vaibhav; Weber, Joseph R.; Malm, Erik; Fouke, Bruce W.; Bulone, Vincent (Frontiers in Plant Science, 2016)
S-acylation is a reversible post-translational modification of proteins known to be involved in membrane targeting, subcellular trafficking, and the determination of a great variety of functional properties of proteins. The aim of this work was to identify S-acylated proteins in poplar. The use of an acyl-biotin exchange method and mass spectrometry allowed the identification of around 450 S-acylated proteins, which were subdivided into three major groups of proteins involved in transport, signal transduction, and response to stress, respectively. The largest group of S-acylated proteins was the protein kinase superfamily. Soluble N-ethylmaleimide-sensitive factor-activating protein receptors, band 7 family proteins and tetraspanins, all primarily related to intracellular trafficking, were also identified. In addition, cell wall related proteins, including cellulose synthases and other glucan synthases, were found to be S-acylated. Twenty four of the identified S-acylated proteins were also enriched in detergent-resistant membrane microdomains, suggesting S-acylation plays a key role in the localization of proteins to specialized plasma membrane subdomains. This dataset promises to enhance our current understanding of the various functions of S-acylated proteins in plants.